A thermal insulation composite board and preparation method thereof
By coating the prepared thermal insulation slurry on the surface of rock wood boards, the problem of poor thermal insulation effect of rock wood boards is solved, the improved thermal insulation performance is achieved, and the application of rock wood boards in special environments is promoted.
Patent Information
- Application Number
- CN202411507056.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-28
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-10-28
AI Technical Summary
The poor thermal insulation effect of rock wood boards limits its application in special environments and affects its promotion.
The thermal insulation slurry is prepared by blending acrylic emulsion, modified filler, dispersant, defoaming agent, film forming additive and deionized water, and coated on the surface of the rock wood board and dried to produce a thermal insulation composite sheet.
The porous structure and dipole moment adsorption mechanism of the modified filler significantly improve the insulation effect of the plate, making it show good thermal insulation performance in special environments.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of thermal insulation composite board preparation, and in particular to a thermal insulation composite board and a preparation method thereof. Background Art
[0002] Rockwood is a special type of wood with unique texture and grain. It is widely used in construction, furniture and other fields due to its excellent properties such as corrosion resistance and wear resistance. These characteristics of rockwood make it an ideal building material that can resist the erosion of various environmental factors and maintain its original beauty and durability. However, the thermal insulation effect of rockwood board materials is not good, which makes it impossible to use rockwood board materials in special environments, thus affecting the promotion of rockwood board materials. Summary of the invention
[0003] The purpose of the present invention is to provide a thermal insulation composite board and a preparation method thereof, which solves the problem that the thermal insulation effect of rock and wood boards at the current stage is poor.
[0004] The purpose of the present invention can be achieved by the following technical solutions:
[0005] A thermal insulation composite board and a preparation method thereof, specifically comprising the following steps:
[0006] Step A1: acrylic acid, n-butyl acrylate, methyl methacrylate, vinyl triethoxysilane and deionized water are uniformly mixed, nitrogen is introduced for protection, and ammonium persulfate is added under stirring at a speed of 150-200 r / min, a temperature of 65-70° C., and a pH of 7.5-8, and the mixture is reacted for 1-2 hours to obtain an acrylic emulsion;
[0007] Step A2: Weigh the following raw materials in parts by weight: 100-120 parts of acrylic emulsion, 45-55 parts of modified filler, 3-5 parts of dispersant, 1-2 parts of defoaming agent, 0.5-1 part of film-forming aid and 40-50 parts of deionized water, mix the acrylic emulsion, modified filler, dispersant, defoaming agent and film-forming aid evenly, stir and add deionized water at a speed of 600-800r / min and a temperature of 60-70°C, stir for 10-15 minutes to obtain thermal insulation slurry, apply the thermal insulation slurry on the surface of the rockwood board and dry it to obtain a thermal insulation composite board.
[0008] Furthermore, the usage ratio of acrylic acid, n-butyl acrylate, methyl methacrylate, vinyl triethoxysilane and deionized water in step A1 is 4mmol:6mmol:2mmol:1mmol:10mL, and the usage of ammonium persulfate is 0.1-0.5% of the total mass of acrylic acid, n-butyl acrylate, methyl methacrylate and vinyl triethoxysilane.
[0009] Furthermore, the dispersant described in step A2 is a mixture of one or more of OP-10, BYK-190 or BYK-191 in any proportion, the defoamer is a mixture of one or more of BYK024, BYK028 or BYK052 in any proportion, and the film-forming aid is a mixture of one or more of ethylene glycol monobutyl ether, propylene glycol monomethyl ether or diethylene glycol monobutyl ether in any proportion.
[0010] Further, the modified filler is prepared by the following steps:
[0011] Step B1: 4-aminobenzoic acid and hydrochloric acid solution are mixed, stirred and sodium nitrite aqueous solution is added at a speed of 120-150 r / min and a temperature of 0-5° C., and the mixture is reacted for 30-40 min. Sodium carbonate and phenol are added, and the reaction is continued for 3-5 h. The pH value is adjusted to 7 to obtain intermediate 1. Intermediate 1, 2-aminoimidazole, dicyclohexylcarbodiimide and DMF are mixed, and the mixture is reacted at a speed of 200-300 r / min and a temperature of 40-50° C. for 4-6 h to obtain an organic ligand;
[0012] Step B2: Mix the organic ligand and DMF evenly, stir and add sodium hydroxide at a speed of 120-150r / min and a temperature of 25-30°C, stir for 10-15min, add zinc nitrate hexahydrate, stir for 10-15min, heat to 150-155°C, react for 20-25h to obtain a zinc organic framework, dissolve triethylenetetramine in deionized water, stir and add lactic acid at a speed of 600-800r / min and a temperature of 0°C, heat to 20-25°C, react for 5-7h, heat to 100°C, and dry until the quality is no longer reduced to obtain an ionic liquid;
[0013] Step B3: Evenly mix the ionic liquid, zinc organic framework and methanol, and stir at a speed of 200-300r / min and a temperature of 25-30°C until the methanol is completely volatilized to obtain a precursor, place the precursor in a reaction kettle, pass carbon dioxide gas to exhaust the air, maintain the pressure at 100-150kPa, and maintain the pressure for 3-5h to obtain a pretreated precursor, evenly mix the pretreated precursor, ethanol, deionized water, polyvinyl pyrrolidone and polyethylene glycol, pass carbon dioxide to exhaust the air, stir and add tetrabutyl titanate at a speed of 120-150r / min and a temperature of 20-25°C, react for 20-25h, filter and dry to obtain a modified filler.
[0014] Furthermore, the dosage ratio of 4-aminobenzoic acid, hydrochloric acid solution, sodium nitrite aqueous solution, sodium carbonate and phenol in step B1 is 10mmol:100mL:5mL:14mmol:10mmol, the concentration of hydrochloric acid solution is 1mol / L, the mass fraction of sodium nitrite solution is 35%, and the molar ratio of intermediate 1, 2-aminoimidazole and dicyclohexylcarbodiimide is 1:1:1.2.
[0015] Furthermore, the molar ratio of the organic ligand, sodium hydroxide and zinc nitrate hexahydrate described in step B2 is 6:1:1, and the amount ratio of triethylenetetramine, deionized water and lactic acid is 1 mol:200 mL:1 mol.
[0016] Furthermore, the dosage ratio of the ionic liquid, zinc organic framework and methanol described in step B3 is 2g:3g:150mL, the dosage ratio of the pretreatment precursor, ethanol, deionized water, polyvinyl pyrrolidone, polyethylene glycol and tetrabutyl titanate is 1g:150mL:1.5mL:2g:2g:2.5mL, the model of polyvinyl pyrrolidone is K30, and the molecular weight of polyethylene glycol is 400.
[0017] Beneficial effects of the present invention: A thermal insulation composite board prepared by the present invention is prepared by copolymerizing acrylic acid, n-butyl acrylate, methyl methacrylate, vinyl triethoxysilane and deionized water to obtain acrylic emulsion, and the acrylic emulsion, modified filler, dispersant, defoaming agent, film-forming aid and deionized water are blended to obtain thermal insulation slurry, and the thermal insulation slurry is coated on the surface of the rockwood board and dried to obtain the thermal insulation composite board.
[0018] The modified filler uses 4-aminobenzoic acid and phenol as raw materials to form an azo structure to obtain an intermediate 1, dehydrates the intermediate 1 and 2-aminoimidazole under the action of dicyclohexylcarbodiimide to obtain an organic ligand, reacts the organic ligand with zinc nitrate hexahydrate to form a zinc organic framework, reacts triethylenetetramine with lactic acid to form an ionic liquid of triethylenetetramine lactate, blends the ionic liquid with the zinc organic framework to load the ionic liquid to obtain a precursor, performs pressure treatment on the precursor in a titanium dioxide atmosphere to obtain a pretreated precursor, and covers the surface of the pretreated precursor with nano-titanium dioxide to obtain a modified filler.
[0019] The addition of modified fillers makes the board have good thermal insulation effects. The interior of the modified filler is a porous structure. Through pressure treatment in a carbon dioxide atmosphere, the air in the pores is replaced by carbon dioxide gas. The organic ligand contains an azo structure. The electronegativity of the point atoms on the azo group is higher than that of the carbon atom, which leads to uneven distribution of electrons in the azo group, so that the azo group has a permanent dipole moment. The carbon dioxide molecule also makes a polar molecule with a dipole moment, so that the azo group can adsorb carbon dioxide well. The ionic liquid is ammonia-rich ionic liquid. The amino group has lone pairs of electrons and can form an interaction force with the oxygen atoms in the carbon dioxide, thereby improving the adsorption effect, so that the interior of the modified filler is filled with carbon dioxide. DETAILED DESCRIPTION
[0020] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0021] Example 1
[0022] A method for preparing a thermal insulation composite board comprises the following steps:
[0023] Step A1: acrylic acid, n-butyl acrylate, methyl methacrylate, vinyl triethoxysilane and deionized water are uniformly mixed, nitrogen is introduced for protection, and ammonium persulfate is added under stirring at a speed of 150 r / min, a temperature of 65° C., and a pH of 7.5, and the mixture is reacted for 1 hour to obtain an acrylic emulsion;
[0024] Step A2: Weigh the following raw materials in parts by weight: 100 parts of acrylic emulsion, 45 parts of modified filler, 3 parts of dispersant, 1 part of defoaming agent, 0.5 parts of film-forming aid and 40 parts of deionized water, mix the acrylic emulsion, modified filler, dispersant, defoaming agent and film-forming aid evenly, stir and add deionized water at a speed of 600 r / min and a temperature of 60°C, stir for 10 minutes to obtain thermal insulation slurry, apply the thermal insulation slurry on the surface of the rockwood board and dry it to obtain a thermal insulation composite board.
[0025] The usage ratio of acrylic acid, n-butyl acrylate, methyl methacrylate, vinyl triethoxysilane and deionized water in step A1 is 4mmol:6mmol:2mmol:1mmol:10mL, and the usage of ammonium persulfate is 0.1% by weight of acrylic acid, n-butyl acrylate, methyl methacrylate and vinyl triethoxysilane.
[0026] The model of the dispersant described in step A2 is OP-10, the model of the defoamer is BYK024, and the film-forming aid is ethylene glycol monobutyl ether.
[0027] The modified filler is prepared by the following steps:
[0028] Step B1: 4-aminobenzoic acid and hydrochloric acid solution are mixed, stirred and sodium nitrite aqueous solution is added at a speed of 120 r / min and a temperature of 0°C, and the reaction is carried out for 30 minutes, sodium carbonate and phenol are added, and the reaction is continued for 3 hours, and the pH value is adjusted to 7 to obtain intermediate 1, and intermediate 1, 2-aminoimidazole, dicyclohexylcarbodiimide and DMF are mixed, and the reaction is carried out at a speed of 200 r / min and a temperature of 40°C for 4 hours to obtain an organic ligand;
[0029] Step B2: The organic ligand and DMF are mixed evenly, and sodium hydroxide is added under the conditions of a rotation speed of 120 r / min and a temperature of 25°C, and stirred for 10 min. Zinc nitrate hexahydrate is added, and stirred for 10 min. The temperature is raised to 150°C, and the reaction is carried out for 20 h to obtain a zinc organic framework. Triethylenetetramine is dissolved in deionized water, and lactic acid is added under the conditions of a rotation speed of 600 r / min and a temperature of 0°C, and the temperature is raised to 20°C, and the reaction is carried out for 5 h. The temperature is raised to 100°C, and the mixture is dried until the quality is no longer reduced to obtain an ionic liquid.
[0030] Step B3: Evenly mix the ionic liquid, zinc organic framework and methanol, and stir at a speed of 200 r / min and a temperature of 25°C until the methanol is completely volatilized to obtain a precursor. The precursor is placed in a reactor, and carbon dioxide gas is introduced to exhaust the air. The pressure is maintained at 100 kPa and the pressure is maintained for 3 hours to obtain a pretreated precursor. Evenly mix the pretreated precursor, ethanol, deionized water, polyvinyl pyrrolidone and polyethylene glycol, and carbon dioxide is introduced to exhaust the air. At a speed of 120 r / min and a temperature of 20°C, stir and add tetrabutyl titanate, react for 20 hours, filter and dry to obtain a modified filler.
[0031] The amount ratio of 4-aminobenzoic acid, hydrochloric acid solution, sodium nitrite aqueous solution, sodium carbonate and phenol in step B1 is 10mmol:100mL:5mL:14mmol:10mmol, the concentration of hydrochloric acid solution is 1mol / L, the mass fraction of sodium nitrite solution is 35%, and the molar ratio of intermediate 1, 2-aminoimidazole and dicyclohexylcarbodiimide is 1:1:1.2.
[0032] The molar ratio of the organic ligand, sodium hydroxide and zinc nitrate hexahydrate described in step B2 is 6:1:1, and the amount ratio of triethylenetetramine, deionized water and lactic acid is 1 mol:200 mL:1 mol.
[0033] The dosage ratio of the ionic liquid, zinc organic framework and methanol described in step B3 is 2g:3g:150mL, and the dosage ratio of the pretreatment precursor, ethanol, deionized water, polyvinyl pyrrolidone, polyethylene glycol and tetrabutyl titanate is 1g:150mL:1.5mL:2g:2g:2.5mL, the model of polyvinyl pyrrolidone is K30, and the molecular weight of polyethylene glycol is 400.
[0034] Example 2
[0035] A method for preparing a thermal insulation composite board comprises the following steps:
[0036] Step A1: acrylic acid, n-butyl acrylate, methyl methacrylate, vinyl triethoxysilane and deionized water are uniformly mixed, nitrogen is introduced for protection, and ammonium persulfate is added under stirring at a speed of 150 r / min, a temperature of 70° C., and a pH of 7.5, and the mixture is reacted for 2 hours to obtain an acrylic emulsion;
[0037] Step A2: Weigh the following raw materials in parts by weight: 110 parts of acrylic emulsion, 50 parts of modified filler, 4 parts of dispersant, 1.5 parts of defoaming agent, 0.8 parts of film-forming aid and 45 parts of deionized water, mix the acrylic emulsion, modified filler, dispersant, defoaming agent and film-forming aid evenly, stir and add deionized water at a speed of 600 r / min and a temperature of 65°C, stir for 15 minutes to obtain thermal insulation slurry, apply the thermal insulation slurry on the surface of the rockwood board and dry it to obtain a thermal insulation composite board.
[0038] The usage ratio of acrylic acid, n-butyl acrylate, methyl methacrylate, vinyl triethoxysilane and deionized water in step A1 is 4mmol:6mmol:2mmol:1mmol:10mL, and the usage of ammonium persulfate is 0.3% of the total mass of acrylic acid, n-butyl acrylate, methyl methacrylate and vinyl triethoxysilane.
[0039] The model of the dispersant described in step A2 is BYK-190, the model of the defoaming agent is BYK028, and the film-forming aid is propylene glycol monomethyl ether.
[0040] The modified filler is prepared by the following steps:
[0041] Step B1: 4-aminobenzoic acid and hydrochloric acid solution are mixed, stirred at a speed of 120 r / min and a temperature of 5° C., and a sodium nitrite aqueous solution is added to react for 35 min, sodium carbonate and phenol are added, and the reaction is continued for 4 h, and the pH value is adjusted to 7 to obtain intermediate 1, and intermediate 1, 2-aminoimidazole, dicyclohexylcarbodiimide and DMF are mixed, and reacted at a speed of 300 r / min and a temperature of 45° C. for 5 h to obtain an organic ligand;
[0042] Step B2: The organic ligand and DMF are mixed evenly, and sodium hydroxide is added under the conditions of a rotation speed of 120 r / min and a temperature of 28°C, and stirred for 15 minutes, zinc nitrate hexahydrate is added, and stirred for 10-15 minutes, and the temperature is raised to 150°C, and the reaction is carried out for 25 hours to obtain a zinc organic framework, triethylenetetramine is dissolved in deionized water, and lactic acid is added under the conditions of a rotation speed of 800 r / min and a temperature of 0°C, and the temperature is raised to 23°C, and the reaction is carried out for 6 hours, and the temperature is raised to 100°C, and dried until the quality is no longer reduced to obtain an ionic liquid;
[0043] Step B3: Evenly mix the ionic liquid, zinc organic framework and methanol, and stir at a speed of 300 r / min and a temperature of 25°C until the methanol is completely volatilized to obtain a precursor. The precursor is placed in a reactor, and carbon dioxide gas is introduced to exhaust the air. The pressure is maintained at 130 kPa and the pressure is maintained for 4 hours to obtain a pretreated precursor. The pretreated precursor, ethanol, deionized water, polyvinyl pyrrolidone and polyethylene glycol are evenly mixed, and carbon dioxide is introduced to exhaust the air. At a speed of 120 r / min and a temperature of 25°C, tetrabutyl titanate is added with stirring, and the reaction is carried out for 20 hours. Then, the mixture is filtered and dried to obtain a modified filler.
[0044] The amount ratio of 4-aminobenzoic acid, hydrochloric acid solution, sodium nitrite aqueous solution, sodium carbonate and phenol in step B1 is 10mmol:100mL:5mL:14mmol:10mmol, the concentration of hydrochloric acid solution is 1mol / L, the mass fraction of sodium nitrite solution is 35%, and the molar ratio of intermediate 1, 2-aminoimidazole and dicyclohexylcarbodiimide is 1:1:1.2.
[0045] The molar ratio of the organic ligand, sodium hydroxide and zinc nitrate hexahydrate described in step B2 is 6:1:1, and the amount ratio of triethylenetetramine, deionized water and lactic acid is 1 mol:200 mL:1 mol.
[0046] The dosage ratio of the ionic liquid, zinc organic framework and methanol described in step B3 is 2g:3g:150mL, and the dosage ratio of the pretreatment precursor, ethanol, deionized water, polyvinyl pyrrolidone, polyethylene glycol and tetrabutyl titanate is 1g:150mL:1.5mL:2g:2g:2.5mL, the model of polyvinyl pyrrolidone is K30, and the molecular weight of polyethylene glycol is 400.
[0047] Example 3
[0048] A method for preparing a thermal insulation composite board comprises the following steps:
[0049] Step A1: acrylic acid, n-butyl acrylate, methyl methacrylate, vinyl triethoxysilane and deionized water are uniformly mixed, nitrogen is introduced for protection, and ammonium persulfate is added under stirring at a speed of 200 r / min, a temperature of 70° C., and a pH of 8, and the mixture is reacted for 2 hours to obtain an acrylic emulsion;
[0050] Step A2: Weigh the following raw materials in parts by weight: 120 parts of acrylic emulsion, 55 parts of modified filler, 5 parts of dispersant, 2 parts of defoaming agent, 1 part of film-forming aid and 50 parts of deionized water, mix the acrylic emulsion, modified filler, dispersant, defoaming agent and film-forming aid evenly, stir and add deionized water at a speed of 800 r / min and a temperature of 70°C, stir for 15 minutes to obtain a thermal insulation slurry, apply the thermal insulation slurry on the surface of the rockwood board and dry it to obtain a thermal insulation composite board.
[0051] The usage ratio of acrylic acid, n-butyl acrylate, methyl methacrylate, vinyl triethoxysilane and deionized water in step A1 is 4mmol:6mmol:2mmol:1mmol:10mL, and the usage of ammonium persulfate is 0.5% of the total mass of acrylic acid, n-butyl acrylate, methyl methacrylate and vinyl triethoxysilane.
[0052] The model of the dispersant described in step A2 is BYK-191, the model of the defoamer is BYK052, and the film-forming aid is diethylene glycol monobutyl ether.
[0053] The modified filler is prepared by the following steps:
[0054] Step B1: 4-aminobenzoic acid and hydrochloric acid solution are mixed, stirred and sodium nitrite aqueous solution is added at a speed of 150 r / min and a temperature of 5° C., and the reaction is carried out for 40 minutes, sodium carbonate and phenol are added, and the reaction is continued for 5 hours, and the pH value is adjusted to 7 to obtain intermediate 1, and intermediate 1, 2-aminoimidazole, dicyclohexylcarbodiimide and DMF are mixed, and the reaction is carried out at a speed of 300 r / min and a temperature of 50° C. for 6 hours to obtain an organic ligand;
[0055] Step B2: The organic ligand and DMF are mixed evenly, and sodium hydroxide is added under the conditions of a rotation speed of 150 r / min and a temperature of 30°C, and stirred for 15 minutes. Zinc nitrate hexahydrate is added, and stirred for 15 minutes. The temperature is raised to 155°C, and the reaction is carried out for 25 hours to obtain a zinc organic framework. Triethylenetetramine is dissolved in deionized water, and lactic acid is added under the conditions of a rotation speed of 800 r / min and a temperature of 0°C, and the temperature is raised to 25°C. The reaction is carried out for 7 hours, and the temperature is raised to 100°C, and dried until the quality is no longer reduced to obtain an ionic liquid;
[0056] Step B3: Evenly mix the ionic liquid, zinc organic framework and methanol, and stir at a speed of 300 r / min and a temperature of 30°C until the methanol is completely volatilized to obtain a precursor. The precursor is placed in a reactor, and carbon dioxide gas is introduced to exhaust the air. The pressure is maintained at 150 kPa and the pressure is maintained for 5 hours to obtain a pretreated precursor. The pretreated precursor, ethanol, deionized water, polyvinyl pyrrolidone and polyethylene glycol are evenly mixed, and carbon dioxide is introduced to exhaust the air. At a speed of 150 r / min and a temperature of 25°C, tetrabutyl titanate is added with stirring, and the reaction is carried out for 25 hours, followed by filtering and drying to obtain a modified filler.
[0057] The amount ratio of 4-aminobenzoic acid, hydrochloric acid solution, sodium nitrite aqueous solution, sodium carbonate and phenol in step B1 is 10mmol:100mL:5mL:14mmol:10mmol, the concentration of hydrochloric acid solution is 1mol / L, the mass fraction of sodium nitrite solution is 35%, and the molar ratio of intermediate 1, 2-aminoimidazole and dicyclohexylcarbodiimide is 1:1:1.2.
[0058] The molar ratio of the organic ligand, sodium hydroxide and zinc nitrate hexahydrate described in step B2 is 6:1:1, and the amount ratio of triethylenetetramine, deionized water and lactic acid is 1 mol:200 mL:1 mol.
[0059] The dosage ratio of the ionic liquid, zinc organic framework and methanol described in step B3 is 2g:3g:150mL, and the dosage ratio of the pretreatment precursor, ethanol, deionized water, polyvinyl pyrrolidone, polyethylene glycol and tetrabutyl titanate is 1g:150mL:1.5mL:2g:2g:2.5mL, the model of polyvinyl pyrrolidone is K30, and the molecular weight of polyethylene glycol is 400.
[0060] Comparative Example 1
[0061] Compared with Example 1, this comparative example uses 2-aminoimidazole to replace the organic ligand, and the other steps are the same.
[0062] Comparative Example 2
[0063] Compared with Example 1, no ionic liquid was added in this comparative example, and the remaining steps were the same.
[0064] Comparative Example 3
[0065] Compared with Example 1, this comparative example uses a precursor instead of a pre-treated precursor, and the remaining steps are the same.
[0066] Comparative Example 4
[0067] Compared with Example 1, this comparative example uses a precursor instead of a modified filler, and the remaining steps are the same.
[0068] According to the standard of JG / T402-2013, the thermal insulation slurry prepared in Examples 1-3 and Comparative Examples 1-4 was used instead of the coating, and the thermal insulation temperature difference test results were shown in the following table:
[0069]
[0070] It can be seen from the above table that this application has a very good thermal insulation effect.
[0071] The above contents are merely examples and explanations of the concept of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the concept of the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.
Claims
1. A method for preparing a thermal insulation composite board, characterized in that: The specific steps include: Step A1: acrylic acid, n-butyl acrylate, methyl methacrylate, vinyl triethoxysilane and deionized water are uniformly mixed, nitrogen is introduced for protection, ammonium persulfate is added for stirring and reaction is carried out to obtain an acrylic emulsion; Step A2: Weigh the following raw materials in parts by weight: 100-120 parts of acrylic emulsion, 45-55 parts of modified filler, 3-5 parts of dispersant, 1-2 parts of defoamer, 0.5-1 part of film-forming aid and 40-50 parts of deionized water, mix and stir the acrylic emulsion, modified filler, dispersant, defoamer and film-forming aid, add deionized water, stir and process to obtain thermal insulation slurry, apply the thermal insulation slurry on the surface of rockwood board and dry to obtain thermal insulation composite board; The modified filler is prepared by the following steps: Step B1: 4-aminobenzoic acid and hydrochloric acid solution are mixed and stirred, and sodium nitrite aqueous solution is added to react, sodium carbonate and phenol are added, the reaction is continued, and the pH is adjusted to neutral to obtain intermediate 1, and intermediate 1, 2-aminoimidazole, dicyclohexylcarbodiimide and DMF are mixed and reacted to obtain an organic ligand; Step B2: Mixing and stirring the organic ligand and DMF, adding sodium hydroxide, stirring, adding zinc nitrate hexahydrate, stirring, heating to react, and obtaining a zinc organic framework; dissolving triethylenetetramine in deionized water, stirring, adding lactic acid, heating to react, and drying until the quality is no longer reduced, and obtaining an ionic liquid; Step B3: The ionic liquid, zinc organic framework and methanol are mixed and stirred until the methanol is completely volatilized to obtain a precursor, the precursor is placed in a reaction kettle, carbon dioxide gas is introduced to expel the air, and pressure treatment is performed to obtain a pretreated precursor, the pretreated precursor, ethanol, deionized water, polyvinyl pyrrolidone and polyethylene glycol are mixed evenly, carbon dioxide is introduced to expel the air, stirred and tetrabutyl titanate is added, after reaction, filtering and drying are performed, and a modified filler is obtained.
2. The method for preparing a thermal insulation composite board according to claim 1, characterized in that: The usage ratio of acrylic acid, n-butyl acrylate, methyl methacrylate, vinyltriethoxysilane and deionized water in step A1 is 4 mmol:6 mmol:2 mmol:1 mmol:10 mL.
3. The method for preparing a thermal insulation composite board according to claim 1, characterized in that: The amount ratio of 4-aminobenzoic acid, hydrochloric acid solution, sodium nitrite aqueous solution, sodium carbonate and phenol in step B1 is 10mmol:100mL:5mL:14mmol:10mmol, and the molar ratio of intermediate 1, 2-aminoimidazole and dicyclohexylcarbodiimide is 1:1:1.
2.
4. The method for preparing a thermal insulation composite board according to claim 1, characterized in that: The molar ratio of the organic ligand, sodium hydroxide and zinc nitrate hexahydrate described in step B2 is 6:1:1, and the amount ratio of triethylenetetramine, deionized water and lactic acid is 1 mol:200 mL:1 mol.
5. The method for preparing a thermal insulation composite board according to claim 1, characterized in that: The amount ratio of the ionic liquid, zinc organic framework and methanol described in step B3 is 2g:3g:150mL, and the amount ratio of the pretreatment precursor, ethanol, deionized water, polyvinyl pyrrolidone, polyethylene glycol and tetrabutyl titanate is 1g:150mL:1.5mL:2g:2g:2.5mL.
6. A thermal insulation composite board, characterized in that: Prepared according to any one of claims 1 to 5.
Citation Information
Patent Citations
Covalent organic framework and ionic liquid composite material and preparation method thereof and application of composite material
CN109894087A
Multifunctional fireproof and explosion-proof plate and preparation method thereof
CN117964313A